ChatGPT as The Future of Discharge Reports? A Perspective from Geriatric Medicine - Sunarti, Sri; Aqil, Faisal Mohammad Rifqi; Ghifary, Muhammad Rifqi Al; Dewi, Ni Luh Arini Sukma; Wella, Nulva (Clinical and Research Journal in Internal Medicine, 2025)
Background: Conventional discharge reports often suffer from inconsistencies, incomplete information, and lack of clarity, impeding effective communication and continuity of care. ChatGPT, a powerful language model based on deep learning techniques, can enhance the quality and efficiency of discharge reports. Aim: This article explores the possibility of using ChatGPT in geriatric medicine specifically, where complex medical conditions and multidimensional care plans are common. ChatGPT can assist in capturing detailed patient histories, comprehensively documenting geriatric syndromes, and incorporating personalized recommendations for geriatric care management. Methods: Using GPT-3, we employed the chatbot to generate a discharge report based on comprehensive patient data. The AI-generated report was compared with the actual discharge report, and the AI's approach was validated by requesting supporting sources. This evaluation aimed to assess the reliability and credibility of the AI-generated discharge report. Discussions: Despite its potential advantages, the integration of ChatGPT into healthcare workflows necessitates addressing various challenges. These include ensuring patient data privacy, validating the accuracy and reliability of generated information, and establishing guidelines for responsible use. Conclusion: ChatGPT holds promise as a transformative technology for improving the quality of discharge reports in geriatric medicine. By leveraging its language processing capabilities, ChatGPT can enhance communication, patient understanding, and care coordination, ultimately leading to better patient outcomes and healthcare efficiency. Future research and collaborative efforts are necessary to fully explore and refine the application of ChatGPT in this context and to ensure its seamless integration into clinical practice.